Predictors of freedom from atrial arrhythmia recurrence after cryoballoon ablation for persistent atrial fibrillation: A multicenter study. (2nd July 2019) - Reissmann, Bruno; Plenge, Tobias; Heeger, Christian‐Hendrik; Schlüter, Michael; Wohlmuth, Peter; Fink, Thomas; Rottner, Laura; Tilz, Roland Richard; Mathew, Shibu; Lemeš, Christine; Maurer, Tilman; Lüker, Jakob; et al.
Abstract: Aims: We sought to assess (1) clinical outcomes of second‐generation cryoballoon (CB) ablation for persistent atrial fibrillation (AF), and (2) the association of baseline and procedural covariates with atrial arrhythmia recurrence (AAR) after ablation. Methods: A total of 135 patients (63 ± 11 years, 96 men [71%]) with persistent AF underwent CB ablation at three experienced electrophysiology centers. Freedom from AAR was estimated with the Kaplan‐Meier method. A Cox proportional‐hazards model was used to estimate the effects of baseline and procedural covariates on the likelihood of AAR. Results: Freedom from AAR at 6, 12, and 18 months was estimated at 91% (95% confidence interval [CI] 86%‐96%), 75% (95% CI, 67%‐83%), and 53% (95% CI, 43%‐65%), respectively. The presence of an implantable cardiac device (Hazard ratio [HR] 3.09; 95% CI, 1.37‐7.00; P  = .007), a left atrial (LA) diameter > 50 mm (HR 1.69; 95% CI, 1.02‐2.79; P  = .043), and absence of antiarrhythmic drug (AAD) therapy before the ablation procedure (HR 3.12; 95% CI, 1.72‐5.64; P  < .001) were associated with AAR. A trend toward an increased risk of AAR was revealed for women (HR 1.73; 95% CI, 0.96‐3.11; P  = .069). Conclusions: CB ablation for persistent AF resulted in freedom from AAR about that reported for RF ablation. The presence of an implantable cardiac device, LA size, and absence of AAD therapy at baseline were associated with the risk of AAR.